Validity and clinical utility of a wrist-worn device against polysomnography - Guo, Junwei; Luo, Jinmei; Xiao, Yi; Huang, Rong (PLOS ONE, 2025)
Objective Sleep-wearable technology has developed rapidly. However, few carried out validation in the real clinical settings. This study aimed to validate the performance of a consumer-grade sleep-tracking device compared to polysomnography (PSG) in participants from sleep clinics. Methods Participants referred to sleep clinic from 2021 to 2023 were recruited. Demographics and sleep questionnaires were also collected. All participants completed the PSG test in a sleep laboratory, along with a smart watch (HUAWEI WATCH GT2) that collected movement and heart rate signals using built-in sensors. Epoch-by-epoch agreement analysis and the Bland-Altman method were applied to evaluate the performance of smart watch. Results 98 participants were included in this study. 82 of them were men, with a mean age of 45.3 ± 10.6 years. The smart watch had a high sensitivity (95.9%), accuracy (87.3%), positive predictive value (72.2%), and relatively low specificity (47.9%) for sleep/wake performance. Sleep staging comparisons were mixed. Comparing to PSG, although smart watch tended to overestimate total sleep time (+28.7 min, P = 0.001), sleep efficiency (+5.94%, P < 0.001), sleep onset latency (+8.53 min, P < 0.001) and underestimate wake after sleep onset (−37.00 min, P < 0.001), acceptable agreement was observed in sleep/wake detection (Kappa coefficient>0.4), total sleep time and sleep efficiency (intraclass correlation coefficient>0.4). This agreement was less satisfactory in patients with OSA or insomnia. Conclusion This study compared the performance of a consumer-grade sleep-tracking device with that of PSG. The HUAWEI WATCH GT2 exhibited high agreement in sleep/wake detection. Such devices could be used as alternatives for successive sleep detection and could provide significant benefits to sleep hygiene with more advanced algorithms in the future.